A heterobimetallic single-source precursor enabled layered oxide cathode for sodium-ion batteries. Issue 76 (5th September 2018) - Li, Maofan; Yang, Kai; Liu, Jiajie; Hu, Xiaobing; Kong, Defei; Liu, Tongchao; Zhang, Mingjian; Pan, Feng
Abstract : A heterobimetallic single-source precursor, NaCo(acac)3, featuring a 1D chain structure was for the first time designed to achieve layered oxide P2-Na x CoO2 with superior rate capability for Na-ion batteries (SIBs). It opens a new avenue to synthesize high-performance layered oxide cathode materials for SIBs. Abstract : A single-source precursor NaCo(acac)3 (acac = acetylacetone) for layered oxide cathodes of sodium-ion batteries (SIBs) is reported here. It features a 1D chain structure, and is prepared in nearly quantitative yield employing commercially available reagents. The complex is stable in open air and tends to dissolve in various strongly polar solvents, including H2 O and methanol. The phase-pure layered oxide cathode material P2-Na x CoO2 for SIBs is obtained through calcining the complex, and exhibits an excellent rate capability, even superior to the recently reported P2-Na x CoO2 microspheres. More analogue complexes could be obtained through cationic replacement for the synthesis of other high-performance layered metal oxides for SIBs.